Oral Contraceptives Are Associated with a Higher Risk of Dental Inflammatory and Bleeding Disorders - Asmaa Sami Jawad (Dentistry 3000)
Objective: Oral contraceptive pills (OCPs) are a prevalent form of contraception, yet their association with potential impacts on gingival and periodontal health remains a subject of interest. Prolonged utilization of OCPs, attributable to elevated pro-inflammatory cytokines and prostaglandins, has been demonstrated to heighten the risk of developing periodontal disease. This heightened risk is hypothesized to result from the presence of hormone receptor-positive cells within gingival tissue. Methods: The cross-sectional study was conducted from January 2023 to March 24. Drug-naïve controls (n = 50) were participants who had not received any pharmaceutical therapy, whereas cases were participants who had received just OCPs (ethinyl estradiol 0.03 mg or levonorgestrel 0.15 mg) for at least six months. Results: Women aged 20–45 were referred to the dentist for a check-up. There were no differences (p > 0.05) between the control and case groups for BMI, blood glucose, fasting, or kidney function tests. However, there were differences (p < 0.05) in cholesterol and liver enzyme levels. According to the study, 30% of cases had localized or chronic periodontitis, while 60% of the participants had a widespread aggressive disease. Additionally, research found higher but not statistically significant amounts of plaque, gingivitis, and bleeding in the case group. Compared to non-users, case women had average probing depths that were deeper. Conclusion: The study found that young women with aggressive gum disease, especially those with generalized aggressive periodontitis, tended to use the pill. These women also had higher levels of plaque.